Evaluación de varios programas de fertilización edáfica en dos híbridos de maíz (2B707) y 2B604) en la zona de Quevedo durante la época de verano. - Vera Miño, Marly Isabel (2013)
This research was conducted during the dry season of 2012 on the property of Mr. Richard Palacios located in the 5 km route Quevedo-El Emplame, belonging to the province of Los Rios. He raised the following objectives a) To assess the efficacy and influence on the performance of various soil fertilization programs in elite corn hybrids 2B707 and 2B604 b) Determine the most appropriate type of fertilizer for each of the genetic material c) Establish the interaction between maize hybrids and type of applied fertilizer program. Was used as seed material 2B707 and 2B604 hybrids and fix Mixture fertilization programs, Urea, Urea; Fertimaíz; YaraMila; Mixpac, MagneSil, Nitropac S; Mixpac, 8-20-20, Magnesil, Urea, muriate of potassium and 10 -30 to 10, MagneSil, Nitropac S, Muriate of potash, getting 14 treatments. Experimental design was used randomized complete block. Test was applied DMS to determine the statistical difference between the hybrid and the Duncan test for the difference between the means of fertilizers and interaction at 95% probability. We assessed plant height and ear position, stem diameter, days to silking, ear length and diameter, number of rows per ear, number of healthy pods, number of ear rot, number of ears unproductive humidity, weight of 100 seeds, grain yield kg / ha. In conclusion it is stated that the hybrid plants showed 2B604 higher, up to 10 cm exceeding the hybrid 2B707, while the hybrid cobs 2B707 had greater length, while applying Mixture fix, Urea, filed Ureas differences of 0.10 and 0.14 cm in diameter cob over other fertilizer treatments. On the weight of 100 seeds, the results show values up Fertimaíz 2.82 g above the control, hybrids 2B604 and 2B707 yields of 6960.5 and 6923.3 kg / ha, were statistically identical. Mixing by applying fix, Urea, it was determined Ureas superior in performance to 1284.20 kg / ha application on 8-20-20, MagneSil, urea, muriate of potash. We recommend planting the hybrid 2B604 for its greater response in grain yield per hectare in the same way using the fertilization program mix fix, Urea, Urea, for its greater effect on ear diameter and grain yield. The economic analysis reflects the increase in performance of up to 1636.76 kg Blend program fix + Urea + Urea by the hybrid 2B604 marginal generating earnings of $ 447.76 versus control MagneSil 8-20-20 + + Urea + Muriate of potash, in the 2B707 hybrid the best contribution to the recorded increase in yield 1321.89 kg generating Fertimaíz with marginal utility of $ 384.65